BRIDGING THE DIGITAL DIVIDE IN CURRICULUM DELIVERY: ASSESSMENT OF THE IMPACT OF TECHNOLOGY AVAILABILITY AND ACCESSIBILITY ON TEACHING AND LEARNING - Atiku, Benedicta Awusi; Gozah, Eric Kwame Austro; Erebakyere, John (International Journal of Research -GRANTHAALAYAH, 2026)
The study assessed the influence of educational technology on teaching and learning in basic schools in the Oti Region, with focus on availability, accessibility, and implementation challenges. Guided by the Technology Acceptance Model and Digital Divide theories, the study employed a concurrent mixed-methods approach. Data were collected from 231 respondents using structured questionnaires and semi-structured interviews. The respondents included 50 teachers, 25 head teachers, 150 students, 5 district education officers, and one regional official. The findings revealed a significant lack of ICT resources, especially in rural schools. Although some urban basic schools had a limited number of computers, they lacked internet access and adequate teacher training, which hindered effective integration of technology into teaching. It concluded that despite these challenges, both teachers and students recognized the potential of ICT to enhance engagement and improve learning outcomes and improvement on availability, accessibility and usage would improve curriculum delivery in the Oti Region. The study therefore recommends increased investment in ICT infrastructure, the training of ICT professionals for basic schools, and policy reforms by the Ghana Education Service to promote digital learning in the Oti Region.